Effect o! paslure rest an nematade larvae avauiabiiuly in the Pantanal Regional Mato Grosso. - Catto, João Batista (Pesquisa Agropecuaria Brasileira, 2013)
Monthly, during a four-rnonth perind, after middle March (end ai lhe rainy season), two tracer weaned calves were put in a rested paddock and were later necropsied. Duting lhe experimental period, paslure was also examined for prnsence and number ai intestant Iarvae. On direct examinado; lhe pasture was posilive urifil three months after rest and lhrough lhe animal exarninalion on lhe fourmonlhs olthn study. II was concluded lhat let lhe paslure rest for twa monlhs during ar aI lhe end ai lhe rainy season stongly reduced lhe availavility of larvae on lhe pasture.